2017
DOI: 10.1016/j.aap.2017.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone conversations, listening to music and quiet (electric) cars: Are traffic sounds important for safe cycling?

Abstract: Listening to music or talking on the phone while cycling as well as the growing number of quiet (electric) cars on the road can make the use of auditory cues challenging for cyclists. The present study examined to what extent and in which traffic situations traffic sounds are important for safe cycling. Furthermore, the study investigated the potential safety implications of limited auditory information caused by quiet (electric) cars and by cyclists listening to music or talking on the phone. An Internet surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 34 publications
2
13
1
1
Order By: Relevance
“…This is in agreement with other studies on cyclists (Ahlstrom et al 2016;Stelling-Konczak et al 2018) as well as on pedestrians (Hyman et al 2010;. On the top of the list of self-reported behaviour adaptations, as a means to compensate for the loss of auditory information, is increased visual attention (Adell et al 2014;Stelling-Konczak et al 2017). Stelling- Konczak et al (2018) found that 21% of the cyclists increased and 57% decreased their visual scanning to the right in intersections, when listening to music.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is in agreement with other studies on cyclists (Ahlstrom et al 2016;Stelling-Konczak et al 2018) as well as on pedestrians (Hyman et al 2010;. On the top of the list of self-reported behaviour adaptations, as a means to compensate for the loss of auditory information, is increased visual attention (Adell et al 2014;Stelling-Konczak et al 2017). Stelling- Konczak et al (2018) found that 21% of the cyclists increased and 57% decreased their visual scanning to the right in intersections, when listening to music.…”
Section: Discussionsupporting
confidence: 88%
“…A limitation with most of these studies is that the participants were not allowed to choose how to integrate the mobile phone task with the cycling task. For example, the cyclists claim that they look around more frequently when using their mobile phone, that they do not use their devices in demanding situations and that they sometimes use one earbud instead of two (Goldenbeld et al 2012;Stelling-Konczak et al 2017). Despite these self-reported claims, observational studies report that cyclists who use their phones make fewer head movements to the right than cyclists who were only cycling (de Waard et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are some other riding behaviors which can also become safety hazards in traffic accidents. For example, Stelling et al [59] studied the auditory perception during collisions and accidents of cyclists when they listened to music or made phone calls [41]. The results showed that listening to music and talking on the phone had negative effects on cyclists’ hearing and attention, and there was a greater risk of traffic accidents.…”
Section: Analysis Of Risky Riding Behavior Characteristics and Infmentioning
confidence: 99%
“…Our findings suggest the need for intervention studies to monitor several certain groups of users, such as students, smartphone gamers, and smartphone music listeners, especially when crossing a street. Moreover, there is an urgent need for music listeners to be aware of the increasing number of quiet electric vehicles [22] that may constitute a silent hazard.…”
Section: Discussionmentioning
confidence: 99%